Perlindungan Hukum Anak Pekerja Migran Indonesia Non-Prosedural di Malaysia - Nairo Rizka Nur Hamzah; Ferry Irawan Febriansyah; Aries Isnandar (LPPM Institut Pendidikan Nusantara Global, 2026)
The phenomenon of Indonesian migrant workers working non-procedurally remains a serious problem, particularly when it involves children as a vulnerable group potentially subject to human rights violations. Children of Indonesian migrant workers in Malaysia often face limited access to education, health services, legal protection, and social security due to their parents' administrative status not being in accordance with procedures. This study aims to analyze the effectiveness of legal protection and the fulfillment of human rights for children of Indonesian migrant workers working non-procedurally in Malaysia. The research method used is empirical legal research (juridical-empirical) with a descriptive analytical approach, through a review of laws and regulations, international legal instruments, and empirical data sourced from relevant research and scientific literature. The results of the study indicate that although Indonesia has a legal framework governing the protection of migrant workers and their families, the implementation of legal protection and the fulfillment of human rights for children of migrant workers is still ineffective. The main obstacles include weak coordination between institutions, limited access to basic services, and the impact of parents' non-procedural status. Therefore, it is necessary to strengthen policies, increase bilateral cooperation, and adopt a human rights-based protection approach to ensure the sustainable fulfillment of the rights of Indonesian migrant workers' children.